Learning Strategies ofr Translating English Texts Into Indonesian Students - Farida Repelita Waty Kembaren; Yusriani Yusriani; Masriyanti Nasution (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Multilingual ability is one of the abilities that is really needed in the global era and industrial era 4.0. One of the most vital international languages ​​is English, because English can connect society with the world in various fields, including education. The method used in this research uses Systematic Literature Review (SLR) to find out the most appropriate method for designing Enterprise architecture in government agencies. This research results in the fact that students are quite familiar with mathematics vocabulary and mathematics learning in English, thus the "comprehension strategies" stage has been carried out quite well. However, it can be seen that P students use a type of word-for-word translation which results in the translation results being less smooth and the meaning less precise in the context of phrases, clauses and sentences. So it can be said that the "production strategies" stage is still not good.